Compliant kagome lattice structures for generating in-plane waveforms - Bird,J; Santer,M; Morrison,J (International Journal of Solids and Structures, 2018)
This paper details the design, manufacture and testing of an adaptive structure based on the kagome lattice geometry – a pattern with well documented interesting structural characteristics. The structure is used to produce in-plane travelling waves of variable length and speed in a flat surface. The geometry and dimensions, as well as the location and compliance of boundary conditions, were optimized numerically, and a pneumatically-actuated working demonstrator was manufactured. Static and dynamic photogrammetric and force measurements were taken. The structure was found to be capable of producing dynamic planar waveforms of variable wavelength with large strains. The lattice structure was then surfaced with a pre-tensioned membrane skin allowing these waveforms to be produced over a continuous plane.